(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Autism represents pervasive development disorder which is defined as presence of abnormal or damaged development manifested prior the third year of age with characteristic form of pathological functioning in all three aspects such as social interactions, communications and with repetitive behaviour (WHO). The essay provided an analysis of the literature which elaborates the autistic spectrum of disorder with emphasizes empathy and systematization – two important dimensions in their functioning and their social interaction. The recommendations that comes out from the analysis of various research are pointing one element as very important and that is an intensive early treatment, application of strategies for stimulating empathy and systematization, but also the influence on the wider public for accepting children with autistic spectrum of disorder in all aspects of social living.